High-durability superlattice wurtzite ferroelectric material and preparation and application thereof

By adopting a stacking structure composed of alternately composed of wurtzite ferroelectric film and AlN film in wurtzite ferroelectric memory, the problems of low durability and leakage current of wurtzite ferroelectric memory are solved, and its durability and breakdown resistance are significantly improved.

CN119876899APending Publication Date: 2025-04-25XIDIAN UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510036246.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Wertzite ferroelectric memory has problems of low durability, leakage current and breakdown resistance, which is difficult to meet the requirements of large-scale commercial applications.

Method used

A stacked structure consisting of alternately alternating wurtzite ferroelectric film and AlN film is used to form a high-durability superlattice wurtzite ferroelectric material. By inserting the AlN film to block dislocation extension and inhibit nitrogen vacancy migration, the durability characteristics of the material are improved.

Benefits of technology

It significantly improves the durability of wurtzite ferroelectric memory, increases the number of read and write operation cycles, reduces leakage current, improves breakdown resistance, and achieves the durability of 109 read and write operation cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876899A_ABST
    Figure CN119876899A_ABST
Patent Text Reader

Abstract

The invention discloses a high-durability superlattice wurtzite ferroelectric material and preparation and application thereof.The high-durability superlattice wurtzite ferroelectric material is of a stacked structure composed of wurtzite ferroelectric films and AlN films alternately, and the total layer number of the stacked structure is larger than two. The first layer and the last layer of the stacked structure are wurtzite ferroelectric films. The preparation method comprises the following steps: depositing a layer of wurtzite ferroelectric film on the substrate; depositing a layer of AlN thin film on the obtained wurtzite ferroelectric thin film; a layer of wurtzite ferroelectric film is deposited on the obtained AlN film; the steps are repeated until a required stacked structure is formed, and the material can be used for a ferroelectric memory. The AlN thin film with good lattice matching performance with the wurtzite ferroelectric thin film is inserted into the wurtzite ferroelectric thin film, so that the durability of the thin film is improved, the superlattice structure shows excellent performance of low defect, low electric leakage, high durability and the like, and the breakdown resistance and durability of the ferroelectric memory are improved when the superlattice structure is applied to the ferroelectric memory.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of memory devices, and in particular relates to a high-durability superlattice wurtzite ferroelectric material and a preparation method and application thereof. Background Art

[0002] Wurtzite ferroelectric memory is a potential choice for in-memory non-volatile memory due to its large storage window, multi-level storage capability, and low thermal budget. However, wurtzite ferroelectric memory still faces the problem of low endurance. Generally, its endurance is usually limited to about 10 5 ~10 7 The MCU has a read-write cycle, which is far below the level required for large-scale commercial applications. At the same time, its breakdown resistance and leakage current characteristics also need to be further improved. Summary of the invention

[0003] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a high-durability superlattice wurtzite ferroelectric material and its preparation and application, so as to solve the problems of low durability and high leakage of wurtzite ferroelectric memory.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] According to a first aspect of the present invention, a high-durability superlattice wurtzite ferroelectric material is provided. The high-durability superlattice wurtzite ferroelectric material is a stacked structure consisting of alternating wurtzite ferroelectric films and AlN films. The total number of layers of the stacked structure is greater than 2 layers, and the first layer and the last layer of the stacked structure are both wurtzite ferroelectric films.

[0006] In one embodiment, the material of the wurtzite ferroelectric film is AlScN ferroelectric material, AlBN ferroelectric material or gallium nitride-based ferroelectric material. For example, the gallium nitride-based ferroelectric material may be GaScN ferroelectric material or GaYN ferroelectric material.

[0007] In one embodiment, the thickness of each layer of the wurtzite ferroelectric thin film is in the range of 5 nm to 30 nm; the thickness of each layer of the AlN thin film is in the range of 5 nm to 20 nm.

[0008] In one embodiment, the total thickness of the high-durability superlattice wurtzite ferroelectric material is in the range of 40 nm to 500 nm. Within this total thickness range, the thickness and number of wurtzite ferroelectric thin film layers and the thickness and number of AlN thin films are selected.

[0009] The second aspect of the present invention provides a method for preparing the high-durability superlattice wurtzite ferroelectric material according to the first aspect, comprising the following steps:

[0010] Step 1, depositing a wurtzite ferroelectric thin film on a substrate;

[0011] Step 2, depositing a layer of AlN film on the wurtzite ferroelectric film obtained in the previous step;

[0012] Step 3, depositing a wurtzite ferroelectric film on the AlN film obtained in the previous step;

[0013] Step 4, repeating steps 2 and 3 until a desired stacking structure is formed.

[0014] The third aspect of the present invention provides application of the high-durability superlattice wurtzite ferroelectric material described in the first aspect in a ferroelectric memory.

[0015] In one embodiment, the ferroelectric memory includes the stack structure, and a bottom electrode and a top electrode respectively disposed on two sides of the stack structure.

[0016] In one embodiment, the ferroelectric memory can be prepared by the following process:

[0017] Step 1, depositing a bottom electrode on a substrate;

[0018] Step 2, depositing a wurtzite ferroelectric thin film on the bottom electrode;

[0019] Step 3, depositing a layer of AlN film on the wurtzite ferroelectric film obtained in the previous step;

[0020] Step 4, depositing a wurtzite ferroelectric film on the AlN film obtained in the previous step;

[0021] Step 5, repeating steps 3 and 4 until a desired multi-layer stacking structure is formed;

[0022] Step 6: sputter deposit a top electrode on the last layer of wurtzite ferroelectric film, and perform photolithography and etching to obtain a ferroelectric memory.

[0023] In one embodiment, a ferroelectric memory array is composed of a single ferroelectric memory as a storage unit, each storage unit is connected to an external electric field through an independent control line, and the polarization direction of the storage unit is controlled by adjusting the direction of the external electric field, so that its state is encoded as a logical "0" or "1". The present invention can achieve data storage with ultra-high erase and write times by improving the durability of a single storage unit.

[0024] Compared with the prior art, the present invention improves the durability of the wurtzite ferroelectric film by inserting an AlN film with good lattice matching performance into the wurtzite ferroelectric film, so that the superlattice structure exhibits excellent properties such as low defects, low leakage, and high durability. Furthermore, when applied to ferroelectric memory, the breakdown resistance and durability of the ferroelectric memory are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic structural diagram of the high-durability superlattice wurtzite ferroelectric material of the present invention.

[0026] Figure 2 It is a schematic diagram of the effect of the AlN film on grain boundary interruption and vacancy migration inhibition in an embodiment of the present invention.

[0027] Figure 3 It is a transmission electron microscope image and an energy dispersive X-ray spectrum of the superlattice structure and AlScN structure of the high-durability superlattice wurtzite ferroelectric material in an embodiment of the present invention.

[0028] Figure 4 It is a schematic diagram of the structure of a ferroelectric memory obtained by the present invention using a high-durability superlattice wurtzite ferroelectric material.

[0029] Figure 5 It is a schematic diagram of a specific preparation process of a ferroelectric memory in an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.

[0031] refer to Figure 1 As shown, the present invention is a high-durability superlattice wurtzite ferroelectric material, which is a stacked structure consisting of at least two layers of wurtzite ferroelectric thin films 1 and at least one layer of AlN thin film 2 alternately, and the first layer and the last layer of the stacked structure are both wurtzite ferroelectric thin films 1. The present invention can reduce the possibility of grain boundaries penetrating the ferroelectric thin film as a whole, reduce the number of leakage channels, and improve the durability of the wurtzite ferroelectric material by inserting the AlN thin film 2.

[0032] Specifically, a superlattice structure refers to a nanostructure composed of two or more different materials with good lattice matching through periodic stacking, and its periodic length is usually several to tens of nanometers. Superlattice is a special case of heterostructure. The present invention uses wurtzite ferroelectric film 1 and AlN film 2 with good lattice matching performance to form a "superlattice" by alternately growing a periodic structure.

[0033] In the conventional thin film deposition process, dislocations are generated in the wurtzite ferroelectric thin film due to lattice mismatch, and these dislocations usually extend to the entire film. In the present invention, by inserting the AlN film 2, the extension path of the dislocations in the entire film can be blocked, and the dislocations can be confined to the single-layer wurtzite ferroelectric thin film 1, thereby reducing the dislocation density in the entire multilayer stacking structure, thereby achieving an improvement in the consistency of crystal orientation and reducing the dislocation density of the entire film.

[0034] In addition, during the deposition process, affected by high temperature, the interface oxide layer and nitrogen vacancies formed by non-in-situ preparation may diffuse along the grain boundaries, resulting in uneven defect concentration distribution in the film, and in the durability test, the formation of leakage channels will be caused by the application of high electric field electrical stress, causing the film to generate excessive Joule heat, resulting in hard breakdown of the film. The present invention forms a periodic superlattice structure by stacking the wurtzite ferroelectric film 1 and the AlN film 2, which can limit the scope of the leakage channel caused by defects, and at the same time, through crystal plane torsion and grain boundary interruption, the superlattice structure exhibits excellent properties such as low defects, low leakage, and high durability.

[0035] In an embodiment of the present invention, the material of the wurtzite ferroelectric film 1 can be AlScN ferroelectric material, AlBN ferroelectric material, gallium nitride-based ferroelectric material, etc., all of which have good lattice matching performance with AlN. For example, the gallium nitride-based ferroelectric material can specifically be GaScN ferroelectric material or GaYN ferroelectric material, etc. It is well known that various ferroelectric materials have certain component ratio requirements. For example, for AlScN ferroelectric material, when the Sc content is 0.1-0.4 based on the total molar amount of Al and Sc, it has a more obvious ferroelectricity. Since this component content is an inherent value as a ferroelectric material, the scope of the component content is no longer described in the present invention.

[0036] In an embodiment of the present invention, assuming that the number of layers of the AlN film 2 is K, the number of layers of the wurtzite ferroelectric film 1 is K+1. K is limited by the precision of the thin film magnetron sputtering equipment and the total thickness of the film size miniaturization. The thinner AlN film 2 helps to form more interfaces, thereby increasing the interface barrier density and enhancing the ability to constrain defects. An overly thick AlN film 2 may reduce the total polarization strength of the superlattice, so it is necessary to reasonably control the thickness of the insertion layer, i.e., the AlN film 2. Under the premise of controlling the total thickness of the material, increasing the number of layers of the AlN film 2 will not only significantly increase the number of interfaces in the superlattice, but also further optimize the ferroelectric properties of the material. Specifically, more AlN films 2 introduce additional interfaces, which help to significantly improve the ratio of the breakdown field strength to the coercive field, thereby enhancing the ability of the thin film material to resist electrical breakdown. In addition, the interface effect can also effectively inhibit the migration of nitrogen vacancies and the generation of leakage current, thereby improving the durability of the film.

[0037] For example, the total thickness of the high-durability superlattice wurtzite ferroelectric material ranges from 40nm to 500nm, which is designed to maintain excellent ferroelectric properties and long-term structural stability at a miniaturized size. This embodiment chooses 190nm, which is a moderate thickness that can achieve reliability and processing compatibility in memory applications. Figure 1In the structure shown, taking K=5 and the material of the wurtzite ferroelectric film 1 being AlScN as an example, the present invention aims to increase the number of interfaces and reduce the propagation rate of deflection electric dendrites to enhance the reliability of the wurtzite ferroelectric film. On the one hand, the AlN film 2 and the AlScN film have good lattice matching characteristics. On the other hand, since the crystal plane twist and grain boundary interruption themselves have obvious effects on the migration of nitrogen vacancies and the suppression of leakage current, the leakage current is significantly reduced and the ratio of the breakdown electric field strength to the coercive electric field is increased. Finally, the durability of the superlattice wurtzite ferroelectric material can be improved by up to 4 orders of magnitude, reaching 10 9 A read and write operation cycle.

[0038] At the same time, AlN film 2, as an insertion layer, can affect defect regulation and interface barriers and inhibit the migration of nitrogen vacancies. Figure 2 As shown in the figure, nitrogen vacancies are common point defects in the wurtzite structure, which have a significant impact on the leakage current, dielectric loss, breakdown field strength and durability of the material. Since the Al-N bond in AlN film 2 is more stable than that in AlScN, the formation energy of nitrogen vacancies in AlN film 2 is higher, which reduces the generation and migration of nitrogen vacancies. The introduction of AlN film 2 will break the continuity of the grain boundaries of AlScN, significantly increase the migration energy barrier, and thus reduce the mobility of nitrogen vacancies.

[0039] In an embodiment of the present invention, the thickness of each layer of the wurtzite ferroelectric film 1 is in the range of 5 nm to 30 nm. Within this thickness range, the good ferroelectric properties of the wurtzite ferroelectric film and the requirements for miniaturization are well balanced. The thickness of each layer of the wurtzite ferroelectric film 1 is further preferably 25 nm. The 25 nm thick wurtzite ferroelectric film provides sufficient and stable ferroelectric polarization while maintaining moderate interface regulation capabilities. The thickness of 25 nm can reduce stress concentration inside the film in the superlattice and form a good lattice match with the AlN film 2. In addition, magnetron sputtering (Sputter) or molecular epitaxy equipment (MBE) or atomic layer deposition equipment (ALD) can accurately control the thickness of 25 nm to avoid lattice defects caused by being too thin.

[0040] In an embodiment of the present invention, the thickness of each layer of AlN film 2 is in the range of 5nm to 20nm. The interface barrier formed in this thickness range is moderate, which can suppress leakage current without significantly reducing the overall polarization performance. And the AlN film 2 in this thickness range can take into account both film uniformity and lattice stability, reducing stress concentration in the structure. The thickness of each layer of AlN film 2 is further preferably 8nm. The thickness of 8nm can more effectively increase the formation energy of nitrogen vacancies and the migration barrier of nitrogen vacancies, significantly reducing the defect concentration. At the same time, the thickness of 8nm is easy to control in magnetron sputtering or molecular beam epitaxy equipment or atomic layer deposition equipment, and can maintain the periodicity and uniformity of the superlattice structure.

[0041] The high-durability superlattice wurtzite ferroelectric material of the present invention can be prepared by the following steps:

[0042] Step 1, depositing a layer of wurtzite ferroelectric film 1 on a substrate; the substrate used in the present invention includes but is not limited to metal or semiconductor substrates such as heavily doped Si, Pt, TiN, W, Mo, sapphire, Ge, etc.

[0043] Step 2: depositing a layer of AlN film 2 on the wurtzite ferroelectric film 1 obtained in the previous step.

[0044] Step 3: depositing a layer of wurtzite ferroelectric film 1 on the AlN film 2 obtained in the previous step.

[0045] Step 4, repeating steps 2 and 3, alternately depositing the wurtzite ferroelectric film 1 and the AlN film 2 with good lattice matching in situ until the desired multilayer stacking structure is formed.

[0046] Figure 3 The HR-TEM and EDS results of AlScN and superlattice (SL) structures are shown. HR-TEM analysis clearly shows that the grain size in the SL structure is significantly larger than that in AlScN, while the grains in AlScN are smaller and the grain boundaries are dense. This high density of grain boundaries will increase the number of leakage channels, resulting in more significant leakage. In contrast, the SL structure has a larger grain size and fewer potential leakage channels, thus showing better electrical properties. In addition, the EDS results further verify that the present invention successfully formed the superlattice stacking structure of AlScN / AlN, proving the effectiveness of precise structural control during the preparation process. Figure 2 and Figure 3 The results shown are based on Al 0.8 Sc 0.2 For AlScN ferroelectric materials with other component contents, the principles are consistent and the results are similar because they have the same ferroelectricity.

[0047] A typical ferroelectric memory can be obtained by using the high-durability superlattice wurtzite ferroelectric material of the present invention, that is, a top electrode 3 is arranged on the top of the superlattice wurtzite ferroelectric material stacking structure, and a bottom electrode 4 is arranged on the bottom of the superlattice wurtzite ferroelectric material stacking structure, such as Figure 4 shown.

[0048] The ferroelectric memory can be prepared by the following steps:

[0049] Step 1: Deposit and prepare a bottom electrode 4 on a substrate. The substrate used in the present invention includes but is not limited to metal or semiconductor substrates such as Si, Pt, TiN, W, Mo, sapphire, and Ge.

[0050] Step 2: depositing a layer of wurtzite ferroelectric thin film 1 on the bottom electrode 4 .

[0051] Step 3: depositing a layer of AlN film 2 on the wurtzite ferroelectric film 1 obtained in the previous step.

[0052] Step 4: depositing a layer of wurtzite ferroelectric film 1 on the AlN film 2 obtained in the previous step.

[0053] Step 5, repeating steps 3 and 4 until a desired multi-layer stacking structure is formed.

[0054] Step 6: sputter-deposit a top electrode 3 on the last layer of wurtzite ferroelectric film 1, and pattern the top electrode 3 by photolithography and etching to obtain a ferroelectric memory.

[0055] Taking the material of the wurtzite ferroelectric thin film 1 as AlScN as an example, Figure 5The specific preparation process is shown, and the process is based on the sputtering process as a whole. First, a semiconductor substrate is selected, and the surface impurities are removed by surface cleaning treatment with acetone ultrasound for 5 minutes and isopropanol ultrasound for 5 minutes, and then the substrate surface oxide is removed by soaking in DHF solution for 1 minute. Then, a bottom electrode 4 is prepared by depositing the bottom metal on the semiconductor substrate. Next, a stacked structure is grown on the bottom electrode 4 by Sputter or ALD process. For the Sputter process, the wurtzite AlScN / AlN superlattice film material is grown by alternating deposition of AlScN film and AlN film by reactive magnetron sputtering in a high temperature and high nitrogen environment of 200 to 400°C while maintaining the high vacuum degree of the equipment. Specifically, the Al-Sc alloy target or the co-sputtering of the Al target and the Sc target is used to adjust the film composition by adjusting the target sputtering power and the nitrogen / argon mixed gas; in the deposition process of the AlScN film, a 5 to 20 nm thick AlN film is deposited by the Al target every 5 to 30 nm of the AlScN film to regulate the grain boundary and reduce the defect state density. For the ALD process, while maintaining a high vacuum degree of the equipment, in a high temperature environment of 300-450°C, appropriate Sc and Al precursors are selected, and ammonia is used as a nitrogen source to alternately deposit AlScN films and AlN films. Finally, a metal electrode such as Pt or TiN is sputtered to prepare a top electrode 3, and the final wurtzite ferroelectric memory is prepared by photolithography and etching.

[0056] In summary, the superlattice structure of the present invention significantly reduces the generation and migration of defects, reduces the leakage current of non-volatile ferroelectric memory, and enhances the breakdown electric field strength, thereby significantly improving the high durability of the device, especially the performance in multiple erase and write operations, ensuring long-term high performance stability. Ultimately, the present invention lays a solid foundation for the storage and computing integration application of high-durability storage technology and ferroelectric memory.

Claims

1. A high-durability superlattice wurtzite ferroelectric material, characterized in that: The high-durability superlattice wurtzite ferroelectric material is a stacked structure composed of wurtzite ferroelectric thin films and AlN thin films alternately, the total number of layers of the stacked structure is greater than 2, and the first layer and the last layer of the stacked structure are both wurtzite ferroelectric thin films.

2. A high-durability superlattice wurtzite ferroelectric material according to claim 1, characterized in that: The material of the wurtzite ferroelectric film is AlScN ferroelectric material, AlBN ferroelectric material or gallium nitride-based ferroelectric material.

3. A high-durability superlattice wurtzite ferroelectric material according to claim 2, characterized in that: The gallium nitride-based ferroelectric material is a GaScN ferroelectric material or a GaYN ferroelectric material.

4. The high-durability superlattice wurtzite ferroelectric material according to claim 1, characterized in that: The thickness of each layer of the wurtzite ferroelectric film is in the range of 5nm to 30nm; the thickness of each layer of the AlN film is in the range of 5nm to 20nm.

5. A high-durability superlattice wurtzite ferroelectric material according to claim 1, 2, 3 or 4, characterized in that: The total thickness of the high-durability superlattice wurtzite ferroelectric material is in the range of 40 nm to 500 nm.

6. The method for preparing a high-durability superlattice wurtzite ferroelectric material according to claim 1, characterized in that: The following steps are involved: Step 1, depositing a wurtzite ferroelectric thin film on a substrate; Step 2, depositing a layer of AlN film on the wurtzite ferroelectric film obtained in the previous step; Step 3, depositing a wurtzite ferroelectric film on the AlN film obtained in the previous step; Step 4, repeating steps 2 and 3 until a desired stacking structure is formed.

7. Application of the high-durability superlattice wurtzite ferroelectric material as claimed in claim 1 in ferroelectric memory.

8. The use according to claim 7, characterized in that: The ferroelectric memory includes the stack structure, and a bottom electrode and a top electrode respectively arranged on two sides of the stack structure.

9. The use according to claim 8, characterized in that: The ferroelectric memory is prepared by the following process: Step 1, depositing a bottom electrode on a substrate; Step 2, depositing a wurtzite ferroelectric thin film on the bottom electrode; Step 3, depositing a layer of AlN film on the wurtzite ferroelectric film obtained in the previous step; Step 4, depositing a wurtzite ferroelectric film on the AlN film obtained in the previous step; Step 5, repeating steps 3 and 4 until a desired stacking structure is formed; Step 6: sputter deposit a top electrode on the last layer of wurtzite ferroelectric film, and perform photolithography and etching to obtain a ferroelectric memory.

10. The use according to claim 8, characterized in that: A ferroelectric memory array is composed of a single ferroelectric memory as a storage unit. Each storage unit is connected to an external electric field through an independent control line. By adjusting the direction of the external electric field, the polarization direction of the storage unit is controlled, thereby encoding its state into logic "0" or "1".

Citation Information

Cited By

  • Sandwich-structure wurtzite ferroelectric material and atomic layer deposition preparation method thereof

    CN121250336A

  • Method for preparing ultrathin wurtzite ferroelectric film through plasma nitriding pretreatment

    CN122428261A

  • Preparation method of nitrogen-vacancy assisted high-durability wurtzite ferroelectric material

    CN122602784A